Installazioni e forme di deriva - Randazzo, Ivana (Aesthetica Preprint, 2021)
Art is one of the most communicative means for exploring environmental problems. It represents a key for stimulating reflection on the salvation of the Earth through considerations that mature from the observation of public art installations. These can be understood and ‘felt’ by each human being, regardless of culture, social class, race or religion. We are surrounded by artworks installations that push us to reflect on the fate of our planet. These site-specific installations around the world contribute to the development of critical thinking on environmental issues, such as global warming and marine pollution with plastic debris.